Chronic depression of hypothalamic paraventricular neuronal activity produces sustained hypotension in hypertensive rats. Issue 1 (4th December 2013) - Geraldes, Vera; Gonçalves‐Rosa, Nataniel; Liu, Beihui; Paton, Julian F. R.; Rocha, Isabel
New Findings What is the central question of this study? Will a chronic reduction of neuronal excitability within the paraventricular nucleus of the hypothalamus reduce arterial blood pressure and sympathetic activity in the long term in an animal model of neurogenic hypertension? What is the main finding and its importance? We show, for the first time, that overexpression of an inwardly rectifying potassium channel in the paraventricular nucleus provided a long‐term (>60 days) antihypertensive response in conscious spontaneously hypertensive rats that was associated with a reduction in neurohumorally mediated vasoconstriction, enhanced baroreflex sensitivity and reduced peripheral chemosensitivity; no such response was observed in normotensive rats. Our results support the paraventricular nucleus as a therapeutic target for the chronic control of blood pressure in neurogenic hypertension. Changes in the sympathetic nervous system are responsible for the initiation, development and maintenance of hypertension. An important central sympathoexcitatory region is the paraventricular nucleus (PVN) of the hypothalamus, which may become more active in hypertensive conditions, as shown in acute studies previously. Our objective was to depress PVN neuronal activity chronically by the overexpression of an inwardly rectifying potassium channel (hKir2.1), while evaluating the consequences on blood pressure (BP) and its reflex regulation. In spontaneously hypertensive rats (SHRs) and Wistar rats (WKY) lentiviral vectors (LVV‐hKir2.1; LV‐TREtight‐Kir‐cIRES‐GFP5 4 × 109 IU and LV‐Syn‐Eff‐G4BS‐Syn‐Tetoff 6.2 × 109 IU in a ratio 1:4) were stereotaxically microinjected bilaterally into the PVN. Sham‐treated SHRs and WKY received bilateral PVN microinjections of LVV‐eGFP (LV‐Syn‐Eff‐G4BS‐Syn‐Tetoff 6.2 × 109 IU and LV‐TREtight‐GFP 5.7 × 109 IU in a ratio 1:4). Blood pressure was monitored continuously by radio‐telemetry and evaluated over 75 days. Baroreflex gain was evaluated using phenylephrine (25 μg ml−1, i.v.), whereas lobeline (25 μg ml−1, i.v.) was used to stimulate peripheral chemoreceptors. In SHRs but not normotensive WKY rats, LVV‐hKir2.1 expression in the PVN produced time‐dependent and significant decreases in systolic (from 158 ± 3 to 132 ± 6 mmHg; P < 0.05) and diastolic BP (from 135 ± 4 to 113 ± 5 mmHg; P < 0.05). The systolic BP low‐frequency band was reduced (from 0.79 ± 0.13 to 0.42 ± 0.09 mmHg2; P < 0.05), suggesting reduced sympathetic vasomotor tone. Baroreflex gain was increased and peripheral chemoreflex depressed after PVN microinjection of LVV‐hKir2.1. We conclude that the PVN plays a major role in long‐term control of BP and sympathetic nervous system activity in SHRs. This is associated with reductions in both peripheral chemosensitivity and respiratory‐induced sympathetic modulation and an improvement in baroreflex sensitivity. Our results support the PVN as a powerful site to control BP in neurogenic hypertension.